Enhancing Customer Brand Love For MSME Muslim Fashion Product In Marketing 6.0 Era: How Electronic Self Branding Playing A Role - Khoirun Nisa Bahri; Abdul Rozak; Raisa Ayu Widyasari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Indonesia is recognized as the country with the world’s largest Muslim population, surpassing many others. Consequently, it is unsurprising that numerous business players have begun focusing on Muslim consumers. One notable aspect worth examining is the significant contribution of Micro, Small, and Medium Enterprises (MSMEs) to the nation’s economic income. West Java, the province with the highest number of MSMEs in Indonesia, is distinguished by several leading subsectors, including culinary, fashion, and crafts. Throughout their development, MSMEs encounter a range of challenges such as low managerial professionalism, limited financial resources, and insufficient technological capabilities. In addition, intensifying market competition compels MSMEs to strengthen consumer brand loyalty. Brand loyalty encourages customers to consistently choose a brand’s products or services over competing alternatives. The adoption of electronic self-branding and active social media engagement is expected to help address the issues faced by Muslim fashion MSMEs in West Java. This study aims to examine the influence of electronic self-branding and active social media involvement on customer brand loyalty among Muslim fashion MSMEs in the region. The study population consists of online consumers aged 18–45 who have previously purchased Muslim fashion MSME products in West Java. Data collected from 250 respondents were processed and analyzed using Structural Equation Modeling (SEM). The findings indicate that both active social media involvement and electronic personal branding have a positive and significant impact on customer brand love.